Peroxidase activity after viral infection and whitefly infestation in juvenile and mature leaves of solanum lycopersicum - Dieng, H.; Satho, T.; Abu Hassan, A.; Aziz, A.; Morales, R.E.; Ab Hamid, S.; Miake, F.; AbuBakar, Sazaly (2011)
Whitefly infestation and the begomoviruses that they transmit have been shown to affect the activities of plant defence proteins, but with no relation to heterophylly, a process of great importance underlying the overall biology of plants. Here, we have assessed the effects of Tomato yellow leaf curl virus (TYLCV) infection on Solanum lycopersicum peroxidase (POD) activity and have examined whether leaves of different ages exhibit differential POD activity in response to infection and infestation with Bemisia tabaci B biotype. We used leaf discs of two ages (juvenile and mature) with two different infection statuses (infected and healthy) to examine the activity of the tomato plant peroxidase using guaiacol as a substrate and taking exposure time into account. S. lycopersicum showed increased POD activity in the presence of TYLCV. The activity of the enzyme was higher in mature than in juvenile leaves. In general, both infected and healthy leaves exhibited greater POD activity during whitefly infestation. In the infested juvenile leaves, POD activity was much lower in the healthy leaves and increased gradually with period of exposure to B. tabaci B infestation. In contrast, the activity of the enzyme remained low in infested mature leaves in both the presence and absence of the virus even with increased exposure time. Determination of the distribution of an insect pest is critical for sampling and management. Leaf age is presumed to be associated with the within-host distribution of the geminivirus vector B. tabaci. Juvenile leaves will usually attract more insects due to increased nutritional value and weaker defences. Our results highlight the importance of leaf age/position on the whitefly - host plant - geminivirus interactions and have important implications for sampling and control strategies.